Considerations of accounting standards that can be used to disclose Cryptographic assets in financial reports - AbdulAzeez, Majida AbdulMajeed (Journal of Economic, Administrative and Legal Sciences, 2022)
Cryptographic assets are a digital form of currency that uses mathematical equations and block chain technology to encrypt data. The popularity of this type of currency has grown exponentially over the past few years due to more people and companies using it despite the refusal of central banks and country authorities to recognize cryptocurrencies as money. However, some companies have begun to accept it as payment for goods and services. It is expected that more people will turn to cryptocurrencies in the future. With this, companies will have to find ways to account for and report them in the financial statements, however, the Financial Accounting Standards Board (FASB) has not yet determined how to account for cryptocurrency, leaving companies without formal guidance on the subject. The purpose of this paper is to present potential accounting policies to display how companies will report cryptocurrencies in the future based on evidence derived from a review of the accounting literature. The need to address digital currency problems was recommended by the International Accounting Standards Board.